2020
DOI: 10.48550/arxiv.2002.02210
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From Data to Actions in Intelligent Transportation Systems: a Prescription of Functional Requirements for Model Actionability

Abstract: Advances in Data Science permeate every field of Transportation Science and Engineering, making it straightforward to imagine that developments in the transportation sector will be data-driven. Nowadays, Intelligent Transportation Systems (ITS) could be arguably approached as a "story" intensively producing and consuming large amounts of data. A diversity of sensing devices densely spread over the infrastructure, vehicles or the travelers' personal devices act as sources of data flows that are eventually fed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 176 publications
0
1
0
Order By: Relevance
“…The literature review has demonstrated that there is an increasing race towards finding the best performing traffic forecasting model. However, model actionability should be the ultimate goal for works in the field, which has not exclusively to do with the precision of the forecasts [230].…”
Section: A Actionability: Adaptive Models and Prediction Confidencementioning
confidence: 99%
“…The literature review has demonstrated that there is an increasing race towards finding the best performing traffic forecasting model. However, model actionability should be the ultimate goal for works in the field, which has not exclusively to do with the precision of the forecasts [230].…”
Section: A Actionability: Adaptive Models and Prediction Confidencementioning
confidence: 99%